Model of formation of social competence of students in the process of studying the disciplines of the humanitarian cycle (Educational Dimension, 2021)
The article analyses the course of implementing the competence approach in modern educational realities, social competence as an integrated complex of partial personality competencies is presented. The interdependence between the orientation of the world economy towards integration and globalization, the appeal to the European system of higher education, defined by the Bologna Process, and the reason for radical changes in the guidelines of the educational paradigm for the competence approach are traced. The didactic aspect of the process of studying humanities by students has been clarified. It has been established that the system of humanitarian disciplines can and should be aimed at developing the structural components of students’ social competencies, which are fully interactive and interdependent, as they have the properties of variability, interdependence, integrativity, social and personal significance. The introduction of the model of formation of social competence is described, which consists of four consistently interconnected blocks, namely: motivational-target, organizational-activity, technological and result-reflective. Each block corresponds to the functions, forms and methods and conditions of effective formation of social competence. The presented model of formation of social competence of students in the process of teaching disciplines of the humanities contains a system of dialectically interconnected elements: purpose, blocks, functions, structural and functional components, didactic conditions, forms, methods, approaches.